The Impact of Leaders and Family Social Support on Work Family Balance and Individual Job Satisfaction - Uli Agustina, Nova; Rasyid Abdillah, Muhammad; Asfar, Ali (SAINS ORGANISASI, 2023)
This study aims to explain the impact of leadership social support on work family balance in health workers at the Kec. Bagan Sinembah. Specifically, this study uses the Work Family Balance mechanism/balance between family and work at work as the psychological mechanism that underlies the relationship between the two variables. By involving 71 respondents who worked as health workers. Sinembah Chart and using SEM-PLS analysis, in which this study found that perceived leadership social support had a positive and significant effect on Work Family Balance, while perceived family social support had a positive and significant effect on Work Family Balance. Furthermore, this study found that Work Family Balance / family and work balance at work mediates the relationship between perceived social support and job satisfaction of Health Workers in Kec. Bagan Sinembah. The managerial implications felt by employees in this study are that social support from leaders can increase job satisfaction, through Work Family Balance, and family social support for Work Family Balance, so as to create Job Satisfaction for Health Workers at the Kec. Bagan Sinembah. Furthermore, this study found that work-family balance at work mediates the relationship between perceived social support and job satisfaction of health workers at the Puskesmas Kec. Bagan Sinembah